PENGARUH PENERAPAN METODE PEMBELAJARAN PRAKTIKUM TERHADAP KETERAMPILAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VIII SMP N 3 SUMBER KABUPATEN CIREBON - lilis kurniawati; Reza Oktiana Akbar; muhamad ali misri (EduMa: Mathematics education learning and teaching, 2015)
Critical thinking can be surely taught and practiced for all educational graders. However, in educational field, it is still few teachers who facilitate students’ mathematics critical thinking. The aims of this study is to know whether the implementation of practical learning method significantly affects students’ mathematics critical thinking skills in learning mathematic at junior high school. The significances of the study are to give students’ active role in learning process, to improve students’ comprehension towards mathematic concept, and to upgrade students’ mathematics critical thinking. This research method is experiment method with design path analysis. The population was taken from all eighth graders which are 265 students of SMP N 3 Sumber period 2014/2015. The, the random sampling was used to gain 44 students of VIII E grade. The technique of data collection including questionnaire and essay test was used. The results of questionnaire showed that 25 or 57 % students gave responses very positively toward the implementation of practical learning method. Then, 19 or 43% students gave positive response toward the implementation of practical learning method. The result of t-test showed that there is a linier relationship between practical learning method and mathematics critical thinking with  = 1,341 X. Coefficient with positive response means that there is a significant relationship between practical learning method and mathematics critical thinking by implementing practical learning methods very often may improve students’ mathematics critical thinking. According to the result of t-test, it is showed that taccount = 6,509 > ttabel = 2,020. It can be concluded that the implementation of practical learning method significantly affect students’ mathematics critical thinking at VIII E grade of SMP Negeri 3 Sumber Kabupaten Cirebon.Keywords : Practical Learning Methods, Critical Thinking Skills